Abandono parental y su influencia en el desarrollo emocional de un adolescente de 14 años - Moran Vera, Maria (2020)
One of the problems that are occurring in our daily lives is the abandonment that parents make to their children, leaving them under the guardianship of a close relative or known people, others even leave them abandoned in any place causing unfavorable problems in emotional development and more exclusively entering the age of adolescence. In the present case study, an adolescent was carried out, who presented behavioral problems with his parents. This is why we proceeded to work with the family subsystem. In addition, the fact that the environment that surrounds the child is of vital importance is emphasized, since at that stage growth and psychic maturation take place, likewise the nexus between mother and child from pregnancy promotes essential development in the subject in terms of his personality. To improve this type of problem, various authors emphasize the use of systemic family therapy, which is why systemic family therapy was applied through which improvement results were obtained for said family who were in family disagreement. Based on the results obtained, it was recommended that there be a greater relationship between their parents so that said adolescent feels trust in them.